2019
DOI: 10.1016/j.fsi.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Mytilus galloprovincialis to challenge with the emerging marine pathogen Vibrio coralliilyticus

Abstract: Vibrio coralliilyticus (V.c.) has emerged as a coral pathogen of concern throughout the Indo-Pacific reef. The interest towards understanding its ecology and pathogenic potential has increased since V.c. was shown to be strongly virulent also for other species; in particular, it represents a serious threat for bivalve aquaculture, being one of the most important emerging pathogen responsible for oyster larval mortalities worldwide. V.c. has a tightly regulated temperature-dependent virulence and it has been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…In a global warming scenario, an increase in the seawater temperature could promote the potential disease outbreaks associated with V. coralliilyticus in mollusks [44]. In the present study, we demonstrated that V. coralliilyticus could cause acute mortalities of adult T. crocea when previous work was mainly focused on mortalities of shellfish larvae caused by V. coralliilyticus [12,45].…”
Section: Discussionmentioning
confidence: 49%
“…In a global warming scenario, an increase in the seawater temperature could promote the potential disease outbreaks associated with V. coralliilyticus in mollusks [44]. In the present study, we demonstrated that V. coralliilyticus could cause acute mortalities of adult T. crocea when previous work was mainly focused on mortalities of shellfish larvae caused by V. coralliilyticus [12,45].…”
Section: Discussionmentioning
confidence: 49%
“…V . coralliilyticus has been reported as a threat to mass mortality of bivalve associated with vibriosis outbreaks 22 . Vibriosis infection events frequently occurred in larval rearing stage of shellfish production hatcheries in the United States, Canada and Mexico, leading to shortages in seed oysters 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Immune roles of the TLRs during ontogeny should not be underestimated: Many marine invertebrate embryos and larvae live in environments rich in microbial pathogens [132,133]. Pathogens cause mortality of embryos and larvae but also provoke anomalies during development [134,135]. Therefore, these embryos and larvae need immune defenses to ght pathogens [133].…”
Section: Discussionmentioning
confidence: 99%